The Perspective of Islamic Psychology as a School - mohammad kavyani Arany (مطالعات اسلام و روانشناسی, 2019)
This research aimed to present an elementary comprehensive framework for Islamic psychology (Quran-Based) as a psychological school. The main question of this research was what kind of content, structure, and roadmap Islamic psychology would have. For replying that question, first, the history and literature of Islamic psychology were collected and then they were reviewed through a theoretical (not statistical) meta-analysis method. Some of the findings include a) the research problems and subjects should be obtained from the Islamic society and texts; b) Islamic psychology has its own basic concepts; c) Islamic psychology has obvious differences and similarities in comparison to contemporary psychology; and d) Islamic psychology has a roadmap which coherently brings together all components of a psychological school (such as definition, subject, method, theoretical objectives, applied objectives, problems, basic concepts, and its relation with other Islamic and human sciences).